Selected aesthetic medicine treatment in patients with autoimmune diseases - a literature review - Łopuszyńska, Inga; Stańczyk, Justyna; Adamowicz, Dominik; Meliksetian, Astrik; Wosińska, Alicja; Pazik, Dorota; Kosecka, Katarzyna; Cieślik, Aleksandra; Jargieło, Anna; Kosieradzka, Karolina (Journal of Education, Health and Sport, 2023)
Introduction Interest in cosmetic procedures has been increasing. Data on practices for correcting aesthetic deficits, including those caused by autoimmune diseases are limited. There are fears of disease reactivation and exacerbation of inflammation after surgery. Aim of the study The aim of the study was to investigate the potential influence and safety of aesthetic medicine treatment - hyaluronic acid, botulinum toxin and breast augmentation with implants in patients with autoimmune diseases. Materials and methods A search was conducted using PubMed and Google Scholar databases. Articles were searched in English using the following key words: autoimmune disease, immunogenicity, inflammation, connective tissue, aesthetic medicine. Results Hyaluronic acid is considered the best filler for cosmetic procedures, mainly due to its lack of immunogenicity. No clinical studies have identified contraindications to the administration of hyaluronic acid-based dermal fillers in patients with inflammatory diseases. Botulinum toxin is essential in alleviating involuntary functions currently associated with dystonia, spasticity, and autonomic disorders. The long-term safety of implants should be assessed concerning genetic and environmental factors and whether the autoimmune disease is in remission.Conclusion With the increasing number of aesthetic procedures using hyaluronic acid, there are more reports of potential adverse events. Most side effects are associated with hypersensitivity reactions. The use of hyaluronic acid products in patients with autoimmune diseases is controversial. However, no clinical studies have identified contraindications to the administration of hyaluronic acid-based fillers. Botulinum toxin is used for healing and pain control in patients with systemic sclerosis who have suffered phalangeal ulcers. Despite epidemiological studies conducted to assess the association between breast implants and autoimmune diseases the results remain inconclusive